2014
DOI: 10.1515/jbcpp-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on a frequency discrimination task in children

Abstract: This evidence suggests that it is more likely that inherent physiological differences between the sexes influence the differential outcomes reported in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…For example, men seem to have a greater ability to ignore taskirrelevant acoustic distractors (Espinoza-Varas & Jajoria, 2009) or to localize target sounds in a multisource sound environment (Lewald & Hausmann, 2013;Zündorf et al, 2011). Also, for preteen children, boys outperformed girls in a frequency discrimination task, which may rather indicate inherent physiological differences between the sexes than socialization effects (Zaltz et al, 2014). We therefore assume that positive results that can be obtained with females are more likely to be generalizable across gender than vice versa, although this would of course need to be tested in further studies.…”
Section: Task and Participantsmentioning
confidence: 99%
“…For example, men seem to have a greater ability to ignore taskirrelevant acoustic distractors (Espinoza-Varas & Jajoria, 2009) or to localize target sounds in a multisource sound environment (Lewald & Hausmann, 2013;Zündorf et al, 2011). Also, for preteen children, boys outperformed girls in a frequency discrimination task, which may rather indicate inherent physiological differences between the sexes than socialization effects (Zaltz et al, 2014). We therefore assume that positive results that can be obtained with females are more likely to be generalizable across gender than vice versa, although this would of course need to be tested in further studies.…”
Section: Task and Participantsmentioning
confidence: 99%
“…A second explanation for the gender disparity originates at the neurophysiological level. Zaltz, Roth, Gover, Liran, and Kishon-Rabin (2014) found significant differences in pitch perception in children (better performances from boys). Investigating both pitch and loudness discrimination, Rammsayer and Troche (2012) also found that men outperformed women, a fact that still held true after controlling for musical training.…”
Section: Discussionmentioning
confidence: 87%
“…Men and women have also been observed to differ in their ability to detect, discriminate, and identify odors (F>M; for a review see Brand & Millot, 2001), to detect sweet, bitter, and sour tastes (F>M; Fikentscher, Roseburg, Spinar, & Bruchmüller, 1977), and to detect touch (F>M; Mogil, 2012;Velle, 1987). Second, the few studies showing sex differences in perception during development are for tasks for which sex differences have been documented in adults: auditory puretone detection (children; Roche, Siervogel, Himes, & Johnson, 1978) and frequency discrimination (children; Zaltz, Roth, Gover, Liran, & Kishon-Rabin, 2014), discrimination of static visual stimuli (infants; Held, Shimojo, & Gwiazda, 1984), detection of the odor of androstenone (adolescents; Dorries, Schmidt, Beauchamp, & Wysocki, 1989), detection of sweetness (infants; Nisbett & Gurwitz, 1970), and the detection of touch (infants; Bell & Costello, 1964).…”
mentioning
confidence: 99%